Welcome to the ZEB REVOlution (GEOmedia, 2016)
GeoSLAM is a manufacturer and supplier of handheld, 3D mobile mappingsystems. Founded in 2012 and headquartered in the UK, GeoSLAM nowhas a global distribution network of 35 distributors across six continents.